Service Recovery and Its Effect on Students’ Satisfaction, Trust, and WOM Communication - Harsono, Soni (Universitas Prasetiya Mulya, 2018)
Service failure is often inevitable; it affects the levels of satisfaction, trust, and WOM. The purpose of this study is to examine the effect of service recovery, by using distributive, procedural, and interactional justice approaches, on students’ satisfaction, trust, and WOM communication at different categories of private universities in East Java. The population is private universities classified in different levels of categories: excellent category, flagship category, and Non-flagship category. The unit analysis is 80-81 students for each university; its total sample is 242 students. Sampling by using an accidental sampling technique, which is based on coincidence. Data analysis using regression assisted by SPSS and WarpPLS program. The results of this study provide university managers in the deep understanding for that service recovery should always be the focus of attention. It is provided that service recovery has an insignificant effect either directly or indirectly on satisfaction, trust, and word of mouth.